Under duress: Suppressing and recovering memories of the Indonesian Sixties - Hearman, Vannessa (Ateneo de Manila University, 2013)
From October 1965, the Indonesian Communist Party (Partai Komunis Indonesia, or PKI) and its followers were brutally repressed after the party’s alleged involvement in a coup attempt. Approximately half a million party members and sympathizers were killed, and hundreds of thousands of them were imprisoned for varying lengths of time. This paper examines how collective memory and a sense of identity were shaped under the conditions of repression and silence that the Suharto regime (1966–1998) imposed on former political prisoners in Indonesia. The survival strategies employed by some former political prisoners, such as assuming new names and new lives, helped obscure the past. In attempting to reconstruct the 1960s as a period of political activism, an obstacle for the researcher has also been the respondents’ difficulties in remembering, as those performing the act of remembering were accustomed to denying and downplaying their political past. At the same time, the regime’s persecution of this group has fostered a community united by a common grievance, and created the outlines of a shared collective memory. Based on research conducted in Indonesia, I reflect on the challenges for oral historians in analyzing memories that have long been suppressed.